Assessment of Exercise Stroke Volume and Its Prediction From Oxygen Pulse in Paralympic Athletes With Locomotor Impairments: Cardiac Long-Term Adaptations Are Possible - Bernardi, Marco; Guerra, Emanuele; Rodio, Angelo; Dante, Donatella; Castellano, Vincenzo; Peluso, Ilaria; Schena, Federico; Bhambhani, Yagesh (Frontiers in Physiology, 2020)
The determinants of cardiac output (CO) during exercise, i.e., stroke volume (SV) and heart rate (HR), could differ in Paralympic athletes (PAthl) with spinal cord injury (SCI) with respect to PAthl with locomotor impairments caused by different health conditions (HC). The purposes of the present study were the comparisons of two groups of PAthl, one with SCI and one with either amputation (AMP) or post poliomyelitis syndrome (PM), assessing the: (1) peak cardiorespiratory responses and determinants (SV and HR) of CO during maximal and submaximal arm cranking exercise (ACE), respectively; (2) correlations between peak oxygen uptake (VO2peak) and the highest SV obtained during submaximal exercise; and (3) correlations between oxygen pulse (O2 pulse, ratio between VO2 and HR) and both SV and O2 arterio-venous difference [(a-v)O2diff]. Each athlete (19 PAthl with SCI, 9 with AMP and 5 with PM) completed a continuous incremental cardiopulmonary ACE test to volitional fatigue to assess peak responses. In a different session CO was indirectly estimated by carbon dioxide (CO2) rebreathing at sub-maximal exercise intensities approximating 30%, 50% and 70% of the VO2peak. There were no significant differences between the PAthl groups in age, anthropometry and VO2peak. However, peak HR was significantly lower and peak O2 pulse was significantly higher in PAthl with AMP/PM compared to those with SCI. During sub-maximal exercise, PAthl with AMP/PM displayed significantly higher SV values (154.8±17.60ml) than PAthl with SCI (117.1±24.66ml). SV correlated significantly with VO2peak in both PAthl with SCI (R2=0.796) and AMP/PM (R2=0.824). O2 pulse correlated significantly with SV in both PAthl with SCI (R2=0.888) and AMP/PM (R2=0.932) and in the overall sample (R2=0.896). No significant correlations were observed between O2 pulse and (a–v)O2diff. It was concluded that in PAthl with different HC: (1) significant differences, as a consequence of the different HC, exist in the determinants of CO at maximal and submaximal ACE; 2) SV is a significant determinant of VO2peak, suggesting cardiac adaptations possible also in PAthl with SCI, (3) SV can be predicted from O2 pulse measurements during submaximal exercise in both groups of PAthl.